Endometrial stromal sarcomas with BCOR‐rearrangement harbor MDM2 amplifications - Felix KF Kommoss; Kenneth TE Chang; Damian Stichel; Ana Banito; David TW Jones; Christoph E Heilig; Stefan Fröhling; Felix Sahm; Albrecht Stenzinger; Wolfgang Hartmann; Gunhild Mechtersheimer; Hans‐Peter Sinn; et al. (Wiley, 2020)
Abstract Recently a novel subtype of endometrial stromal sarcoma (ESS) defined by recurrent genomic alterations involving BCOR has been described (HGESS‐BCOR). We identified a case of HGESS‐BCOR with a ZC3H7B‐BCOR gene fusion, which harbored an amplification of the MDM2 locus. This index case prompted us to investigate MDM2 amplification in four additional cases of HGESS‐BCOR. Tumors were analyzed for MDM2 amplification by array‐based profiling of copy number alterations (CNAs) and fluorescence in situ hybridization (FISH), as well as for MDM2 expression by immunohistochemistry (IHC). Additionally, a cohort of other mesenchymal uterine neoplasms, including 17 low‐grade ESS, 6 classical high‐grade ESS with YWHAE‐rearrangement, 16 uterine tumors resembling ovarian sex cord tumors, 7 uterine leiomyomas and 8 uterine leiomyosarcomas, was analyzed for CNAs in MDM2. Copy number profiling identified amplification of the 12q15 region involving the MDM2 locus in all five HGESS‐BCOR. Subsequent validation analyses of three tumors confirmed MDM2 amplification using MDM2 FISH. Accordingly, IHC showed MDM2 overexpression in all analyzed cases. None of the other uterine neoplasms in our series, including tumors that are in the histopathological differential diagnoses of HGESS‐BCOR, showed copy number gains of MDM2. Together, our results indicate that HGESS‐BCOR carries MDM2 amplifications, which has diagnostic implications and could potentially be used for targeted therapies in these clinically aggressive tumors.